ROLE OF HYPOXIA INDUCIBLE FACTOR-1? IN LYMPH NODE METASTASIS OF BREAST CANCER - Widowati, Galuh (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
Background: Lymph node metastasis in breast cancer is a clinical parameter used to predict a patient’s prognosis. Lymph node metastasis is affected by numerous factors, one of which is hypoxic conditions that trigger the expression of HIF-1?, a transcription factor expressed by cells in hypoxia. To date, the role of HIF-1? in lymph node metastasis in breast cancer requires further research. Objective: This review aimed to describe the possible role of HIF-1? in breast cancer lymph node metastasis. Methods: PubMed and Google Scholar databases were searched for articles using Boolean operations with keywords related to HIF-1? expression and lymph node metastasis of breast cancer. We have limited the 10 years of publication to be included in this review. Results: HIF-1? has the potential to induce epithelial-mesenchymal transition, extracellular matrix invasion, matrix degradation, and lymphangiogenesis through various target gene expression and signaling pathways, leading to lymph node metastasis of breast cancer cells.